Construction of NiCo2O4@graphene nanorods by tuning the compositional chemistry of metal–organic frameworks with enhanced lithium storage properties. Issue 40 (3rd October 2018) - Jia, Zhiqing; Tan, Yingbin; Cui, Zhonghui; Zhang, Linlin; Guo, Xiangxin
Abstract : NiCo2 O4 @graphene nanorods synthesized by tuning the compositional chemistry of metal–organic frameworks exhibit high Li-storage capacity, excellent rate capability and extraordinary cycling stability. Abstract : A novel metal–organic-framework (MOF) composition-tuning strategy has been developed for the synthesis of well-defined hierarchical structures, which is based on reactivity modification of the zeolitic imidazolate framework (ZIF)-67. Typically, 1D ZIF-67@Ni-1, 3, 5-benzenetricarboxylic acid (ZIF-67@Ni-BTC) nanorods are obtained, which can be easily transformed into 1D graphene-coated NiCo2 O4 (NiCo2 O4 @graphene) nanorods by an annealing treatment in an argon atmosphere, followed by oxidation in ambient air. By controlling the reaction time, novel structures such as hollow ZIF-67@Ni-BTC polyhedra and hollow ZIF-67@Ni-BTC polyhedra/ZIF-67@Ni-BTC nanorods can also be achieved. By virtue of the advantages of the structure and graphene coating, NiCo2 O4 @graphene nanorods as lithium storage materials exhibit high Li-storage capacity, excellent rate capability and remarkable cycling stability.